(untitled) (The Research of Medical Science Review, 2025)
This research paper explores the widespread effects of environmental pollutants on the health of livestock, emphasizing the pathological results and wider ramifications for food safety and agriculture. Through systematic analysis, we identified key toxins commonly present in agricultural environments such as heavy metals, pesticides, and mycotoxins. Case studies from different areas show a variety of severe health impacts in livestock including immunosuppression, reproductive failure, and heightened disease susceptibility. Histopathological analyses showed substantial tissue damage and malfunction, establishing a connection between visible clinical symptoms and toxin exposure. The implications of these findings extend beyond individual animal health; they raise concerns about food quality, economic losses for farmers, and potential threats to human health through the food chain. The study further emphasizes on the necessity of strong regulatory frameworks and monitoring mechanisms to reduce cattle exposure to toxins. Ultimately, fostering collaboration among policymakers, farmers, and researchers is essential to safeguard livestock health, ensure food safety, and promote environmental sustainability within agricultural systems, thereby enhancing resilience to future ecological challenges.